PENGARUH DIGITAL PEDAGOGICAL COMPETENCE DAN DIGITAL TEACHING INNOVATION TERHADAP KEMAMPUAN GURU MENGEMBANGKAN CRITICAL THINKING SISWA - Cantika, Melvi; Majid, Nuur Wachid Abdul (JS (JURNAL SEKOLAH), 2025)
Abstract: This research seeks to examine how digital teaching skills and innovative teaching methods affect educators' capacity to enhance students' critical thinking abilities. The approach adopted is a quantitative method featuring a causal associative framework, utilizing a survey method that involves distributing structured questionnaires to all instructors at SMAN 1 Bungursari, with a total of 36 participants. The tool for data collection was validated through Product Moment correlation, while its consistency was evaluated using Cronbach's Alpha. The analysis of the data encompasses classical assumption assessments, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that Digital Pedagogical Competence does not significantly impact teachers' capability to foster Critical Thinking Skills in students (Sig. = 0. 856 > 0. 05), whereas Digital Teaching Innovation does have a meaningful positive impact (Sig. = 0. 026).  Keyword: digital pedagogical competence, digital teaching innovation, critical thinking, teachers, 21st-century learning Abstrak: Riset ini memiliki tujuan untuk mengkaji pengaruh dari kompetensi pedagogi digital dan inovasi pengajaran digital terhadap kemampuan guru dalam mengembangkan critical thinking siswa. Metode Penelitian yang dipakai adalah metode kuantitatif dengan desain asosiatif kausal, serta teknik survei melalui penyebaran kuesioner tertutup kepada seluruh guru di SMAN 1 Bungursari, dengan melibatkan 36 responden. Instrumen penelitian divalidasi menggunakan korelasi Product Moment, sedangkan reliabilitasnya diukur dengan Cronbach's Alpha. Analisis data meliputi uji asumsi klasik, analisis regresi linier berganda, uji-t, uji-F, dan koefisien determinasi (R²). Temuan penelitian menunjukkan bahwa digital pedagogical competence tidak memiliki pengaruh yang signifikan terhadap kemampuan guru dalam meningkatkan Keterampilan Berpikir Kritis siswa (Sig. = 0,856 > 0,05), sedangkan digital teaching innovation memiliki pengaruh positif yang signifikan (Sig. = 0,026). Kata Kunci: kompetensi pedagogik digital, inovasi pengajaran digital, berpikir kritis, guru, abad ke-21.